Observation of Photoelectron Circular Dichroism Using a Nanosecond Laser. Issue 11 (9th May 2019) - Kastner, Alexander; Ring, Tom; Braun, Hendrike; Senftleben, Arne; Baumert, Thomas
Abstract: Photoelectron circular dichroism (PECD) is a fascinating phenomenon both from a fundamental science aspect but also due to its emerging role as a highly sensitive analytic tool for chiral recognition in the gas phase. PECD has been studied with single‐photon as well as multi‐photon ionization. The latter has been investigated in the short pulse limit with femtosecond laser pulses, where ionization can be thought of as an instantaneous process. In this contribution, we demonstrate that multi‐photon PECD still can be observed when using an ultra‐violet nanosecond pulse to ionize chiral showcase fenchone molecules. Compared to femtosecond ionization, the magnitude of PECD is similar, but the lifetime of intermediate molecular states imprints itself in the photoelectron spectra. Being able to use an industrial nanosecond laser to investigate PECD furthermore reduces the technical requirements to apply PECD in analytical chemistry. Abstract : Observation of PECD with a nanosecond laser : Photoelectron circular dichroism is a pronounced forward‐backward asymmetry in photoelectron emission, when chiral molecules are ionized by circularly polarized light. This effect has so far been investigated by synchrotron or fs laser sources. Here, we demonstrate PECD using an ordinary nanosecond laser system, which reduces the technical requirements to apply PECD in analytical chemistry.